Orchestrating warfighting
1 online resource.
Keywords: "Orchestrating Warfighting provides a detailed and wide-ranging examination of the employment of corps and divisions from the First World War through to the early twenty-first century. Orchestrating Warfighting examines British, Dominion, and imperial corps and divisions, taking part in the total wars of the first half of the twentieth century and smaller scale conflicts since 1945. It throws new light on questions of command, generalship, and the management of battles and campaigns across a diverse range of theatres. Orchestrating Warfighting is of interest to historians of the British Army, operational military history, and modern war"--